2013 IEEE Globecom Workshops (GC Wkshps) 2013
DOI: 10.1109/glocomw.2013.6825153
|View full text |Cite
|
Sign up to set email alerts
|

Improved E-model for monitoring quality of multi-party VoIP communications

Abstract: Abstract-Maintaining good Quality-of-Experience (QoE) is crucial for Voice-over-IP (VoIP) applications, particularly those operating across the public Internet. Accurate online estimation of QoE as perceived by end users allows VoIP applications take steps to improve QoE when it falls below acceptable levels. ITU-T recommendation G.107 introduced the E-model, which provides a means to assess QoE levels for two-party VoIP sessions. In this paper we provide an analysis of the accuracy of the E-model for multi-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Table 8 gives an exemplary overview of QoE prediction models that are relevant for telemeetings. To the best of the authors' knowledge, those models have not been validated yet for different types of telemeetings and in particular not for multiparty settings, with the exception of Adel et al [329], who investigated the performance of ITU-T Rec. G.107, the E-Model, [115] for codec tandems that occur in central-bridge-based telemeeting systems.…”
Section: B Instrumental Objective Quality Evaluationmentioning
confidence: 99%
“…Table 8 gives an exemplary overview of QoE prediction models that are relevant for telemeetings. To the best of the authors' knowledge, those models have not been validated yet for different types of telemeetings and in particular not for multiparty settings, with the exception of Adel et al [329], who investigated the performance of ITU-T Rec. G.107, the E-Model, [115] for codec tandems that occur in central-bridge-based telemeeting systems.…”
Section: B Instrumental Objective Quality Evaluationmentioning
confidence: 99%
“…Hoeldtke and Raake defined in 2011 a new state model for MVoIP calls and applied statistical measures to recordings made during a three-party conferencing quality test, which was designed to evaluate the perceived quality under various speech transmission properties [7]. In 2013, Adel et al showed that the G.107 E-model is inaccurate in measuring the QoE of MVoIP calls and thus they proposed an improved E-model specifically designed for MVoIP sessions, which produces results very similar to the PESQ scores [8].…”
Section: Related Workmentioning
confidence: 99%